Development and biological evaluation of Ti6Al7Nb scaffold implants coated with gentamycin-saturated bacterial cellulose biomaterial - Dydak, Karolina (PLoS One, 2018)
Herein we present an innovative method of coating the surface of Titanium-Aluminium-Niobium bone scaffold implants with bacterial cellulose (BC) polymer saturated with antibiotic. Customized Ti6Al7Nb scaffolds manufactured using Selective Laser Melting were immersed in a suspension of Komagataeibacter xylinus bacteria which displays an ability to produce a 3-dimensional structure of bio-cellulose polymer. The process of complete implant coating with BC took on average 7 days. Subsequently, the BC matrix was cleansed by means of alkaline lysis and saturated with gentamycin. Scanning electron microscopy revealed that BC adheres and penetrates into the implant scaffold structure. The viability and development of the cellular layer on BC micro-structure were visualized by means of confocal microscopy. The BC-coated implants displayed a significantly lower cytotoxicity against osteoblast and fibroblast cell cultures in vitro in comparison to non-coated implants. It was also noted that gentamycin released from BC-coated implants inhibited the growth of Staphylococcus aureus cultures in vitro, confirming the suitability of such implant modification for preventing hostile microbial colonization. As demonstrated using digital microscopy, the procedure used for implant coating and BC chemical cleansing did not flaw the biomaterial structure. The results presented herein are of high translational value with regard to future use of customized, BC-coated and antibiotic-saturated implants designed for use in orthopedic applications to speed up recovery and to reduce the risk of musculoskeletal infections.